6q deletion in Waldenström macroglobulinemia is associated with features of adverse prognosis - Enrique M. Ocio; Roelandt F.J. Schop; B. Gonzalez Gonzalez; Scott A. Van Wier; Jesús María Hernández‐Rivas; Norma C. Gutiérrez; Ramón García‐Sánz; Manuel Moro; Carmen Aguilera; Jesús María Hernández‐Rivas; R. Xu; Philip R. Greipp; et al. (2006)
Summary Fluorescence in situ hybridisation (FISH) is an effective technique for the cytogenetic analysis of Waldenström macroglobulinemia (WM), but the potential impact of molecular cytogenetics on disease evolution and as a prognostic marker is still unknown. Deletion of the long arm of chromosome 6 (6q−) is the most frequent cytogenetic abnormality in WM. This study analysed the prevalence of this aberration in 102 WM patients, and correlated it with disease characteristics. The incidence of 6q21 deletion was 7% by conventional cytogenetics and 34% when analysed by FISH (54% when cytoplasmic immunoglobulin M‐FISH was used). Patients with deletion of 6q displayed features of adverse prognosis, such as higher levels of β 2‐microglobulin and monoclonal paraprotein and a greater tendency to display anaemia and hypoalbuminemia. Interestingly, there was a correlation between the presence of 6q deletion and the International Staging System prognostic index (incidence of 6q− among patients stratified in stages 1, 2 and 3 was 24%, 42% and 67% respectively). Those patients diagnosed with smouldering WM who displayed the abnormality showed a trend to an earlier requirement of treatment. Finally, the survival analysis did not show differences between the two groups of patients, probably due to the short follow up of our series.